Wonder Woman. - Picoult, Jodi 1966- (DC Comics, 2007)
Wonder Woman, in her disguise as Diana Prince, a special agent of the Department of Metahuman Affairs, takes on an assignment to track down Wonder Woman, an impossible task that risks revealing her secret identity.